A Prospective Evaluation of Point of Care Ultrasound Teaching in Switzerland - Byrne, Connor (J Med Ultrasound, 2019)
CONTEXT: As the utility of point-of-care ultrasound (POCUS) continues to expand in the medical field, there is a need for effective educational methods. In Switzerland, medical education follows the European model and lasts 6 years, focusing on preclinical training during the first 2 years. No previous studies have evaluated the optimal time for teaching ultrasound in European medical education. AIMS: The aim of this study is to provide ultrasound training to medical students in Switzerland at varying times during their clinical training to determine if the level of training plays a role in their ability to comprehend and to apply basic POCUS skills. METHODS: We performed an observational study utilizing a convenience sample of Swiss medical students between July 11, 2016 and August 6, 2016. They were taught a 2-day POCUS course by five American-trained 1(st)-year medical students. Following this course, students were evaluated with written and clinical examination. RESULTS: 100 Swiss medical students were enrolled in the study. A total of 59 of these students were early clinical students, and 41 students were late clinical students. A two-tailed t-test was performed and demonstrated that the late clinical students performed better than the early clinical students on the written assessment; however, no difference was found in clinical skill. CONCLUSION: Our data suggest that Swiss medical students can learn and perform POCUS after a 2-day instructional taught by trained 1(st)-year American medical students. No difference was found between students in early clinical training and late clinical training for the ability to perform POCUS.